2015
DOI: 10.1080/13603124.2014.987180
|View full text |Cite
|
Sign up to set email alerts
|

Performing the principal: school leadership, masculinity and emotion

Abstract: In western democracies, the critiques of managerialism in school leadership are increasingly common. Feminist researchers have suggested that this recent orientation fits more easily with traditional male leadership than with that of their female counterparts. However, not all men principals are happy with the managerialist turn either. This study investigated how male primary school principals describe their work and respond to the recent changes. While we acknowledge that female principals are also required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…The domination of males leads to discrimination against females (Shakeshaft, 1993). Some males assume that certain gender roles are natural and normal (Hill, Miller, Benson & Handley 2016), while females are subjected to a patriarchal culture, where most of the responsibilities belong to males (Bush & West-Bumharn, 1994;Cundiff & Vescio, 2016;Gill & Arnold, 2015). As Hill, Miller, Benson & Handley (2016) show, whereas men are socialized to be confident, assertive, and self-promoting, cultural attitudes toward women as leaders continue to suggest to women that it is often inappropriate or undesirable to possess those characteristics.…”
Section: Gender and School Leadershipmentioning
confidence: 99%
“…The domination of males leads to discrimination against females (Shakeshaft, 1993). Some males assume that certain gender roles are natural and normal (Hill, Miller, Benson & Handley 2016), while females are subjected to a patriarchal culture, where most of the responsibilities belong to males (Bush & West-Bumharn, 1994;Cundiff & Vescio, 2016;Gill & Arnold, 2015). As Hill, Miller, Benson & Handley (2016) show, whereas men are socialized to be confident, assertive, and self-promoting, cultural attitudes toward women as leaders continue to suggest to women that it is often inappropriate or undesirable to possess those characteristics.…”
Section: Gender and School Leadershipmentioning
confidence: 99%
“…The study observed the attitudes of male principals towards these women and found that most male principals believed that these women overcame their ‘inadequacies’ in order to become principals, however, their ability to do the job well was still questioned. Gill and Arnold (2015) studied the perceptions male principals had of their role, commenting on the struggles they experienced managing emotions, for example, and the expectation that they not appear too emotional. These principals maintained themselves as ‘performing an appropriate masculinity while dealing with the messy uncontrollable force of emotion’ (p. 30).…”
Section: Hegemonic Masculinity and Principalshipmentioning
confidence: 99%
“…Artiklar med fokus på Genus och skolledarskap uppgår till två där aspekter av kvinnligt ledarskap (Thorpe, 2018) samt maskulinitet (Gill & Arnold, 2015) undersöks. I temat för Policy, styrning och inspektion hittar vi en artikel vilken undersöker relationen mellan utbildningspolicy och samverkan med vårdnadshavare (Quesel, Näpfli & Buser, 2017).…”
Section: öVriga Temanunclassified